About causes of early-stage asymptomatic prostate cancer - Ilarion Draguta (The Moldovan Medical Journal, 2017)
Background: The neurotransmitters (epinephrine and norepinephrine) of the sympathetic nervous system that perform numerous cellular and tissue functions contribute to tumor growth during the early stages of development. At the same time, these bioactive substances act as mediators of the descending antinociceptive system that cause inhibition of pain at the suprasegmental and segmental levels of the neurotransmission. Later studies point to the involvement of afferent sensory neurons in tumor process. The functionality of these structures can be changed due to the structural features caused by genetic disorders of myelin. In addition to that, tumor augmentation of sensory neurons endings leads to the involvement of myeloid-derived suppressor cells in the affected area and the creation of an immunosuppressive microenvironment. At the same time, in the secondary inflammatory process, various enzymes that change the cellular matrix and cause invasion and metastasis are released. In addition to sensitizing cytokines, immunocompetent cells – macrophages, neutrophils, lymphocytes – can also produce opioid peptides that target the desensitization of peripheral nociceptors. Opioid peptides inhibit the excitability of sensory nerves without central unwanted side effects such as depression of breathing, clouding of consciousness, or addiction. This peripheral antinociceptive system with ICC may allow the neoplasm to remain asymptomatic for a while. The changes in afferent impulses at the central level in oncopathology can also be associated with those in the functionality of Toll-like receptors. Conclusions: Taking into account the aforementioned literature data about oncogenesis, it may be assumed the presence of a new complex pathogenetic pattern that ensures the asymptomatic evolution of prostate cancer. A better coverage of this data may facilitate further search for early markers of the disease.